Implementation Of Protocol Services In Supporting The Activities Of The Enrekang Regent - Slamet Briutli; Nurlinah Nurlinah; Kurniaty Kurniaty (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
The purpose of this study was to find out the efforts of the Enrekang Regency government in maximizing protocol aspects to succeed in every activity and an official event of the 2022 Enrekang Regent. The research method is to use a mixed methods approach. The research population is the recipients of protocol services. The research sample found as many as 78 respondents. The research results show that resources, mandates, and protocol functions are crucial aspects in the implementation of protocol services in supporting the activities of the Regent of Enrekang. Nonetheless, this study found the assessment results on the implementation identified as less than optimal. There are several influential aspects, including human resources issues, communication, and management of protocol activities. This tendency requires accommodative action, namely performance evaluation by the protocol leadership. Evaluation can be done to anticipate and minimize the same errors that may occur in the future. This is also necessary to continue to support every activity of the Regent of Enrekang.